Primary Amebic Meningoenciphalitis (PAM) - Sutiono, Dias Rima; Aisyah, Siti (Cermin Dunia Kedokteran, 2017)
Naegleria fowleri is one of free-living amoeba that can be found around the world. It is also known as the causative agent of Primary Amebic Meningoencephalitis (PAM). PAM is a rare Central Nervous System (CNS) infection and can lead to fatal outcome. Since the first discovery, it becomes the problem worldwide. Misdiagnoses are common in PAM patient. The causative agent of PAM is living in the warm freshwater. Thus, the occurrence of this infection is high in summer and warmest season through the year. Due to its living characteristics, this amoeba has the potential to live in the Indonesia waters. The purpose of this review is to describe the difference between PAM and bacterial meningitis, epidemiology, diagnosis and prevention of PAM.Naegleria fowleri adalah salah satu amuba yang hidup bebas dan dapat ditemukan di seluruh dunia. N. fowleri dikenal sebagai agen penyebab Primary Amebic Meningoencephalitis (PAM). PAM merupakan infeksi langka yang menyerang sistem saraf pusat (SSP) dan dapat fatal. Sejak ditemukan telah menjadi masalah global. PAM sering salah didiagnosis. Agen penyebab PAM hidup di air tawar hangat; kejadian infeksi tertinggi saat cuaca terpanas. Karakteristik tersebut sesuai dengan iklim di Indonesia. Kajian ini diharapkan mampu menggambarkan perbedaan antara PAM dan meningitis yang disebabkan bakteri, epidemiologi, diagnosis dan pencegahan PAM.